Time for a change: considering the rights of study participants to ownership of their personal research-grade genomic data. (31st December 2018) - Lu, Alice; Kuhn, Peter; Deichaite, Ida
Abstract: Determining the ownership of a patient's personal genomic data is important because it impacts how data is governed and shared, which has both clinical and research implications for precision oncology. The 21st Century Cures Act enacted in December 2016 defined the ownership of clinical genomic data, but the governance of research-grade genomic data remains a hotly contested topic. The many stakeholders often have competing perspectives about ownership of raw and processed genomic data derived in research settings and how to weigh risks versus benefits of sharing this data with study participants. A growing number of research studies, policy recommendations, and ethics reviews have not been enough to influence changes in practice. Most genomic research is conducted in academia, which is guided by Institutional Review Board-approved protocols to protect study participants. The current standard is to limit the return of research-grade data to study participants, and give data ownership solely to the researchers or the research institution, since this data is not vetted for clinical purposes and is meant for research use only. However, these practices conflict not only with recommendations from peer-reviewed literature on best practices for addressing research study participants' needs but might indeed run counter to legal and ethical guidelines about data ownership. For example, patient-participants faced with poorly understood or incurable diseases such as certain cancers want, and could potentially benefit from, having access to their personal genomic data in this rapidly evolving field. This commentary highlights the gap between the status quo as approved by the IRB and the literature suggesting that study participants should be given access to their personal genomic data. There is an opportunity to facilitate a more effective and ethical way to collect genomic data for research use across institutions.